Immediate effects of the respiratory stimulation on ventilation parameters in ischemic stroke survivors: A randomized interventional study (CONSORT). Issue 38 (September 2019) - Ptaszkowska, Lucyna; Ptaszkowski, Kuba; Halski, Tomasz; Taradaj, Jakub; Dymarek, Robert; Paprocka-Borowicz, Malgorzata
Abstract: Background: Post-stroke brain damage, which affects the central control of respiration, leads to various respiratory disorders. They can be caused by the weakening of the respiratory muscles and chest movements, which can indirectly contribute to an impairment of the ventilation function. The aim of the study is an objective assessment of the effect of a single-session intervention of respiratory stimulation through Proprioceptive Neuromuscular Facilitation (PNF) on chosen respiratory parameters and the following comparison of these changes with a group in which positioning was used (intra- and intergroup comparison). Methods: This was a randomized interventional study evaluating the respiratory parameters depending on the applied respiratory stimulation in patients after ischemic stroke. The patients qualified to participate in the study were randomly assigned to 1 of 2 groups: PNF-treated group – in which respiratory stimulation through PNF was used, PNF untreated group – in which positioning was used. The research procedure consisted of several stages. First, an interview was conducted with each participant and basic data was collected. Then, spirometry was conducted, after which each patient underwent a single-session intervention according to their assigned group. Finally, the patients were given another spirometry examination. The main outcomes will be to compare the results of a spirometry test (FVC, FEV1, FEV1/ FVC%, PEF) before and after single-session intervention and between groups. Results: Based on the inclusion and exclusion criteria for the study, 60 patients took part in the measurement. The values of FEV1/FVC% were higher in PNF-treated group than in PNF-untreated group, if the post-intervention measures ( P  = .04) are considered. The difference between the pre- and post-intervention results of the FEV1/FVC% values in PNF-untreated group was substantially lower than in PNF-treated group ( P  = .001). Conclusion: A single application of respiratory stimulation through PNF positively affect air flow in the respiratory tract. Application of PNF stimulation contributed to an increase in the FEV1/FVC% parameter. However, no positive changes were noted in the other parameters, which would provide proof of the beneficial effect of facilitation on the respiratory system function.